Basics for Improved Use of Phages for Therapy - Philip Serwer; Elena T. Wright; Jorge De La Chapa; Cara B. Gonzales (MDPI AG, 2021)
Blood-borne therapeutic phages and phage capsids increasingly reach therapeutic targets as they acquire more persistence, i.e., become more resistant to non-targeted removal from blood. Pathogenic bacteria are targets during classical phage therapy. Metastatic tumors are potential future targets, during use of drug delivery vehicles (DDVs) that are phage derived. Phage therapy has, to date, only sometimes been successful. One cause of failure is low phage persistence. A three-step strategy for increasing persistence is to increase (1) the speed of lytic phage isolation, (2) the diversity of phages isolated, and (3) the effectiveness and speed of screening phages for high persistence. The importance of high persistence-screening is illustrated by our finding here of persistence dramatically higher for coliphage T3 than for its relative, coliphage T7, in murine blood. Coliphage T4 is more persistent, long-term than T3. Pseudomonas chlororaphis phage 201phi2-1 has relatively low persistence. These data are obtained with phages co-inoculated and separately assayed. In addition, highly persistent phage T3 undergoes dispersal to several murine organs and displays tumor tropism in epithelial tissue (xenografted human oral squamous cell carcinoma). Dispersal is an asset for phage therapy, but a liability for phage-based DDVs. We propose increased focus on phage persistence-and dispersal-screening.